Patients with rheumatic disease experiencing ST-elevation myocardial infarction have increased inflammatory- and neurohormonal response and higher 1-year mortality. (2nd May 2022) - Frydland, M; Moeller, JE; Holmvang, L; Goetze, JP; Jensen, LO; Hassager, C
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): This work was supported by Righospitalets Forskningsfond (Grant number: 07IO). Lundbeck Foundation (R186-2015-2132). Background: Patients with rheumatoid diseases have been reported to have increased risk of ST-elevation myocardial infarction (STEMI). However, little is known about mortality risk following STEMI in these patients. Furthermore, STEMI patients with increased neurohormonal- and inflammatory response have higher mortality compared to patients with low response. Purpose: We sought to assess whether patients with a rheumatic disease (RD) have an increased inflammatory- and neurohormonal response to a STEMI and whether 1-year mortality was higher in these patients compared to patients without rheumatic disease. Methods: In 1700 consecutive STEMI patients (comatose cardiac arrest- and cardiogenic shock patients were excluded) from two Danish tertiary heart centres were studied. Biomarkers reflecting neurohormonal activation (pro-atrial natriuretic peptide (proANP), copeptin, and mid-regional pro-adrenomedullin (MRproADM)) and inflammatory response (C-reactive protein (CRP) and ST2) were measured at in the catheterization laboratorium before the acute coronary angiogram was performed. Patients were stratified according to known RD or not. Results: In total, 88 (5.2%) STEMI patients had a RD diagnosis. From these 28 (32%) had RA, 9 (10%) had psoriasis arthritis, and 23 (26%) had gout, while 28 (32%) had other RDs. Patients in the two groups were similar of age (no RD vs. RD, mean (SD): 63 (13) vs. 65 (14) years, p=0.22), mostly male (n (%) 1194 (74) vs 57 (66), p=0.08) with similar number of comorbidities, same LVEF (median (IQR) 50 (40-55) vs. 50 (40-55), p=0.58), and similar infarct size (maximum troponin T concentration 3050 (1150-6885) vs. 3030 (1500-7260) ng/L, p=0.79). In RD patients, admission concentration of MRproADM (median (IQR) 0.77 (0.63-0.98) vs. 0.71 (0.58-0.90) nmol/L, p=0.04), ST2 (43 (33-64) vs 39 (29-55) ng/ml, p=0.04), and CRP (6.8 (2.9-14) vs 3.3 (1.4-8.2) mg/L, p<0.0001) was higher compared to patients without RD. No difference in proANP and copeptin was detected. One-year all-cause mortality was higher in patients with RD (11% vs. 5.5%, p=0.02). When including patients with CS and patients comatose after cardiac arrest, the signal remained intact. Conclusion: STEMI patients with RD have higher admission inflammatory response and neurohormonal activation compared to patients without. Furthermore, patients with RD have higher 1-year all-cause mortality.